Examining the Effects of Relationship Education for Same-Sex Couples: A Randomized Control Trial. Issue 4 (19th May 2022) - Barden, Sejal M.; Carlson, Ryan G.; Toomey, Thomas; Locklear, Lauren; Taylor, Dalena Dillman; Silverio, Nicole
Abstract: Relationship education programs are designed to enhance a variety of relationship characteristics related to building knowledge and skills for healthy relationships. Same-sex couples represent a high-risk group that would benefit from relationship education based on unique challenges such as heterosexist discrimination that impact relationships and the mental health of individuals who identity as sexual minorities. The aim of this investigation was to examine the efficacy of relationship education on improving dyadic coping, emotional regulation, and psychological distress for same-sex couples ( N  = 52) who were enrolled in a randomized control trial testing PREP's Within Our Reach . Results indicate significant positive effects on individual distress symptoms for couples assigned to the intervention. Implications and suggestions for future research are provided.